Digital Marketing Majestic Koi Farm Through Sosial Media Instagram - Sari, Dewi Fitria; Aesthetika, Nur Maghfirah (Procedia of Social Sciences and Humanities, 2024)
Based on the researcher will examine social media marketing related to the concept of content used in Majestic Koi Farm's social media instagaram, the researcher aims to describe the content strategy used by Majestic Koi Farm to obtain research novelty. In this study, the research method is used the approach shown where the research describes the facts, facts, fields, and properties of objective traits accurately based on data derived from the results of observations through the Instagram account on a business. This data collection technique is also carried out through research on the analysis of instagaram social media content. The object of this study is Majestic Koi Farm's Instagram, while the subject in this study focuses on Majestic Koi Farm. The results of the research based on analysis through Instagram social media show that Majestic Koi Farm has implemented a social media marketing strategy in its Instagram. Through the use of Instagram, Majestic Koi Farm has successfully influenced consumers and increased their sales.